2015
DOI: 10.1186/s13071-015-1076-y
|View full text |Cite
|
Sign up to set email alerts
|

Baseline susceptibility to alpha-cypermethrin in Lutzomyia longipalpis (Lutz & Neiva, 1912) from Lapinha Cave (Brazil)

Abstract: BackgroundGiven the increase in cases of visceral leishmaniasis in recent years, associated with the socio-economic impact of this disease, as well as the wide distribution of Lutzomyia longipalpis in Brazil and the likelihood that this vector may develop resistance to insecticides used for control, the Ministry of Health considers as crucial the creation of a network in order to study and monitor the resistance of this vector to insecticides used for control. In this sense, this study aimed: 1) to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…longipalpis, with most, but not all [ 27 , 44 , 45 ] of these studies on Lu. longipalpis from Brazil and in particular from Minas Gerais State [ 20 , 21 , 28 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…longipalpis, with most, but not all [ 27 , 44 , 45 ] of these studies on Lu. longipalpis from Brazil and in particular from Minas Gerais State [ 20 , 21 , 28 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…(i) the discriminating concentrations and baseline susceptibility times to different insecticides for Lu. longipalpis colonies have not been fully established [ 21 , 24 , 46 ]. Although it is reasonable to use those from similar genera, they cannot be extrapolated from other insect groups such as Anopheles mosquitoes [ 26 , 39 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, a number of WHO/CDC dose–response bioassay studies have been conducted in Brazil, Peru, Venezuela, and Colombia, in order to define the LC values (LC 50 , LC 95 , or LC 99 ) for L . longipalpis [ 93 ], Lutzomyia evansi [ 94 , 95 ], and Lutzomyia peruensis [ 96 ] field populations against commonly used insecticides. The respective test values are given in S1 Table .…”
Section: Methodsmentioning
confidence: 99%
“…This was the first record of an insecticide tolerance of sandfly species in South America. Pessoa et al 14 after testing sandflies from Gruta da Lapinha indicated this population as a susceptible reference lineage, as it complies with the requirements of The Pan American Health Organization 14 . More recently, González et al 15 tested populations of Lu.…”
mentioning
confidence: 87%